Effect Size Analysis of the Problem based Learning Model on Students’ HOTS Ability and Conceptual Understanding - Ade Mayasari; Wandika Wandika; Anisa Dwita Fitri (Journal of Innovative Physics Teaching, 2023)
Students' high ability is needed in their learning and daily life. However, students' high-level skills and conceptual understanding were still low. The purpose of this study was to determine the effect size of applying the problem-based learning (PBL) model to students' HOTS skills and conceptual understanding. This type of research is meta-analysis research. The subjects of this study were 20 articles published by several Sinta accredited journals concerning the effects of the problem-based learning model on HOTS skills and students' conceptual understanding. The research instrument is coding. Methods of data analysis using quantitative descriptive analysis with guidelines for effect sizes. After getting the effect size value, the value can then be entered into the effect size level or category. From the results of data analysis, it can be stated that the application of the PBL model has a positive effect on various student abilities based on educational level and type of ability. Thus, the application of the PBL model is effective for increasing mastery of Hots concepts and skills based on educational level.